Shape recognition application (SRA) / Abdul Rahman Ismail - Ismail, Abdul Rahman (2015)
The project is about to develop computer application for recognizing shape. This project focuses on a basic shape like square, circle, oval, rectangle and a triangle. This project is developed for children as they're learning in knowing type of shape. This project has been developed by using MATLAB software and its library, Image Processing Toolbox. The project has used a simple mathematical formula in MATLAB to recognize shapes. The result return is fully accurate for those five shapes, but for other some shape is not. The application cannot recognize the shape like hexagon, pentagon, parallelogram and trapezoid. The image file is accepted as input and the image with a label of result (shape name) is returned as output. The type of image file support for this application was .jpeg, .jpg, .png, and .bmp only. The maximum of image file accepted is 1024 pixel by 1024 pixel. If the input image chosen exceed the maximum size, the result will get bugged and the output image will exceed viewed boarder.